2001
DOI: 10.1007/s004120000123
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale chromatin fibers of living cells display a discontinuous functional organization

Abstract: We investigated the chromatin organization of living cells with a combination of recently developed approaches for histone and DNA labeling. Nucleosomal DNA was labeled with a histone H2B-GFP (green fluorescent protein) fusion protein and the chromatin organization of living HeLa cells was analyzed by high resolution confocal microscopy. Within the perinuclear and perinucleolar regions chromatin was organized into large-scale fibers of 2 to 8 microm in length and 300 to 500 nm in diameter. Within the nuclear i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 35 publications
3
10
0
Order By: Relevance
“…9g and h). Similar nuclear arrangements of SC35, nucleoli, H4K8ac, and transcriptionally active and heterochromatic domains, as observed here in chicken HD12 cells, have been observed in a great variety of different vertebrate cell types when cultivated as monolayers (see for instance (Moen et al 1995;Sadoni et al 1999;Sadoni et al 2001)). .…”
Section: Nuclear Organization Of Non-neural Chicken Monolayer Cellssupporting
confidence: 84%
See 1 more Smart Citation
“…9g and h). Similar nuclear arrangements of SC35, nucleoli, H4K8ac, and transcriptionally active and heterochromatic domains, as observed here in chicken HD12 cells, have been observed in a great variety of different vertebrate cell types when cultivated as monolayers (see for instance (Moen et al 1995;Sadoni et al 1999;Sadoni et al 2001)). .…”
Section: Nuclear Organization Of Non-neural Chicken Monolayer Cellssupporting
confidence: 84%
“…Nuclear organization of the splicing factor SC35 and of active isoforms of RNA Pol II As chromatin-depleted regions are often enriched in splicing factors and represent splicing speckles in monolayer cells (Moen et al 1995;Sadoni et al 2001), which are associated with GC-and gene-rich DNA (Shopland et al 2003), we wondered whether the central DNA-depleted zone in RS nuclei might also be enriched in splicing factors. As the essential splicing factor SC35 is typically enriched in splicing speckles, we performed immunostaining of RS with a specific antibody against SC35.…”
Section: Overall Organization Of Chromatin and Nucleoli In Rs Nucleimentioning
confidence: 99%
“…Bar ϭ 0.5 m. has been described both as a solenoid and as a zigzag conformation (Bednar et al 1998). On the other hand, the 250-300-nm cord is similar to a level of chromatin folding found in both late-replicating heterochromatic homogeneously staining regions (HSRs), which are several hundreds of mega-base pairs in size , and in living cells (Sadoni et al 2001). …”
Section: Figurementioning
confidence: 86%
“…GC-rich DNA was found to be evenly distributed throughout chromosome territories, whereas AT-rich sequences were found statistically more often in the territory interior (Tajbakhsh et al 2000). The comparison of DAPI staining and H2B-GFP labeled chromatin showed that these two methods recognize different portions of the chromatin (Sadoni et al 2001). However, DAPI-stained AT-rich regions concentrate around the nucleoli and at the nuclear periphery (Saccone et al 2002) and are known to coincide with parts of heterochromatic regions (Minc et al 1999).…”
Section: Discussionmentioning
confidence: 95%